Formation of nano-quasicrystalline decagonal phase in the ai 70cu 10co 5ni 15 system by high energy ball milling - Yadav T.P.; Mukhopadhyay N.K.; Shaz M.A.; Tiwari R.S.; Srivastava O.N. (My University, 2025)
A nano decagonal quasicrystalline phase in the Al 70Cu 10Co 5Ni 15 alloy has been synthesized by mechanical alloying of a mixture of elemental powders followed by annealing. A high-energy ball milling of the elemental mixture of Al, Cu, Co and Ni leads to the formation of B2 type quaternary intermetallic alloys. The X-ray diffraction and transmission electron microscopy techniques have been employed for characterization of the samples. It was observed that the dissolution of the individual elements into an alloy led to the formation of a nano B2 phase. This phase was found to be quite stable against milling and no other crystalline or amorphous phases could be detected. Milled powder after annealing at 700 °C for 60 h was found to transform to nano-decagonal phase. Attempts have been made to understand the evolution of the complex intermetallic nano phases and their relative stability during milling. Copyright © 2009 American Scientific Publishers All rights reserved.